The impact of digital technology innovation on ESG performance: Evidence from A-share listed companies in China - Wu Yuanbang (SHS Web of Conferences)
The notion of Environment, Social and Governance (ESG) underscores the necessity for businesses to prioritize non-financial aspects such as environmental preservation, social accountability, and corporate governance while striving for economic advantages. The implementation and utilization of digital technologies have greatly enhanced the ESG performance of firms. This study investigates the influence of corporate digital technology innovation on corporate environmental, social, and governance (ESG) performance. The analysis is based on a sample of A-share listed businesses throughout the period from 2013 to 2022. The results demonstrate that the rise in the level of corporate digital technology innovation has a notable beneficial effect on ESG performance, particularly among companies that are not heavily reliant on technology. Furthermore, this increase is more readily apparent. Furthermore, the two-step method confirms that the implementation of corporate digital technology innovation can enhance ESG performance through optimization of operational efficiency and minimization of agency costs. Furthermore, the enhancement of ESG performance also exerts a positive influence on company performance and helps to alleviate financing limitations. The results of this study offer fresh insights and pragmatic recommendations for organizations to enhance sustainability during the digital transformation process.